Cu (II), Cd (II) and Zn (II) adsorption by the Cuare Mangrove Peat, Falcon State, in different degrees of artificial maturation - Martínez, Virginia; Martínez, Manuel; Reategui, Katya; Escobar, Marcos (Rev. Téc. Fac. Ing. Univ. Zulia)
The high adsorption capacity of peat for heavy metals constitutes a complex phenomenon of economic and environmental interest. Nevertheless, little is known about how this process is modified by enhancing the thermal maturity of the peat, as a consequence of the burial of the peat-bog. The aim of this study is the evaluation of the variability in the capacity of adsorption of the peat for the ions Cu++, Cd++ and Zn++ according with the thermal maturity increases, by means of artificial maturation in the laboratory. The adsorption isotherms were determined in both the original and artificial matured peat, from the peat-bogs of Cuare swamp (Falcon State, Venezuela). Notable decrease is observed in the matured peat for all studied ions, with respect to the original peat. The affinity order for metals towards the carbonaceous materials used was Cu2+> Zn2+> Cd2+.